2012
DOI: 10.1371/journal.pone.0040375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Sex in the Diagnosis of Type 2 Diabetes Using Glycated Haemoglobin in Japan: The Yuport Medical Checkup Centre Study

Abstract: BackgroundWe examined how the prevalence of individuals diagnosed with diabetes differs by age and sex using the diagnostic criteria of fasting plasma glucose (FPG) and/or glycated haemoglobin (HbA1c) in a large Japanese population.MethodsWe conducted a cross-sectional study using a dataset of 33,959 people (16,869 men and 17,090 women) without known diabetes who underwent health checkups from 1998 to 2006. We divided the age range of the participants into six groups of similar numbers. We compared the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…Although there is no population-based data that are directly comparable to those of the present study, two Japanese studies reported the prevalence of diabetes using both HbA1c and FPG criteria in a population without known diabetes; 7.5% in men and 3.4% in women aged 15-93 years, who were community residents and voluntarily participated in a health screening [13], and 3.6% in both men and women aged 18-91 years, who were mainly government employees and underwent health screenings including comprehensive medical examination [14]. The prevalence of diabetes in the present study was similar to that in the former study [13] but appears to be higher than that in the latter [14], a difference that might be due to higher health consciousness of participants in the latter study. In another Japanese study among community residents of Hisayama using 75 g-OGTT, age-specific prevalence of diabetes was 7.5% and 3.9% in men and women, respectively, aged 40-49 years and 19.5% and 9.1% in men and women, respectively, aged 50-59 [21].…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Although there is no population-based data that are directly comparable to those of the present study, two Japanese studies reported the prevalence of diabetes using both HbA1c and FPG criteria in a population without known diabetes; 7.5% in men and 3.4% in women aged 15-93 years, who were community residents and voluntarily participated in a health screening [13], and 3.6% in both men and women aged 18-91 years, who were mainly government employees and underwent health screenings including comprehensive medical examination [14]. The prevalence of diabetes in the present study was similar to that in the former study [13] but appears to be higher than that in the latter [14], a difference that might be due to higher health consciousness of participants in the latter study. In another Japanese study among community residents of Hisayama using 75 g-OGTT, age-specific prevalence of diabetes was 7.5% and 3.9% in men and women, respectively, aged 40-49 years and 19.5% and 9.1% in men and women, respectively, aged 50-59 [21].…”
Section: Discussionmentioning
confidence: 47%
“…If diabetes is defined using FPG criterion and current medication combined, 15% and 23% of total diabetes patients will be missed in men and women, respectively. Women appear to be more likely to be missed than men if HbA1c is not used, as was suggested in previous Japanese and US studies [13,23]. Although the reason is unclear, iron deficiency might partly explain the difference.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In 2011, the World Health Organization and the American Diabetic Association accepted HbA1c levels ≥6.5% as a diagnostic criterion for diabetes mellitus (6,7). However, it is important to take age, race/ethnicity, anemia/hemoglobinopathies (and other diseases for which HbA1c may be an unsatisfactory criterion for the diagnosis of type 2 diabetes) into consideration when using the HbA1c levels to diagnose diabetes (8)(9)(10)(11)(12)(13)(14)(15). Further studies are thus required to promote a more appropriate standard for HbA1c in the diagnosis of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%